Submission to Omai Commission of Enquiry - LaRose, Jean...[et al] ([s.n.] [S.l], 1995)
Expresses concern over a lack of a normative framework of regulatory standards for development in mining and forestry in Guyana. Makes recommendations with regard to the Omai mine.